EVALUATION OF K-EPSILON MODEL FOR TURBULENT BUOYANT JET - Osman Abu Bakr Mohmmed Ahmed; Mark Ovinis (Platform, a Journal of Engineering, 2019)
The modelling of a turbulent buoyant jet is challenging due to the complex nature of such flow, which consists of two fluids with different densities, as well as the multi-scale flow phenomena associated in both space and time. In this paper, the k-epsilon turbulence model is applied to model a turbulent buoyant jet at different flow regimes including laminar and turbulent. The velocity field and centerline velocity are in good agreement with the experiments, as well as the expected results based on jet theory. Moreover, the distribution of the radial velocity matches with Gaussian distribution. The k-epsilon model is an appropriate turbulent model that can be applied for larger Reynolds number flow simulation.